ANALISIS SIKAP KONSUMEN DI KOTA BOGOR DALAM MEMILIH KARTU IM3 OOREDOO SEBAGAI LAYANAN OPERATOR SELULER - Novrianti, Dian Puspita (Jurnal Manajemen Magister Darmajaya, 2015)
This study aimed to analyze the attitudes of consumers in the city of Bogor in choosing IM3 Ooredoo as a mobile operator services. The sampling method used is purposive sampling with judgmental sampling method. The number of samples used in this study was 170 respondents. Testing of this study using the model of Fishbein method of data analysis through factor analysis and ANOVA. The results of this study indicate that the dimension attributes of products considered by consumers in the city of Bogor in choosing IM3 Ooredoo as a mobile operator services can be grouped into three factors, namely product features, network quality factor, and the factor of price and service. Other findings from the study also showed that overall there was no difference in consumer attitudes based on the criteria of the demographic characteristics of respondents, where the value of significance (p value) greater than a = 0.05. This shows that in general consumers in the city of Bogor have the same attitude in choosing IM3 Ooredoo as a mobile operator services.Â Keywords: Consumer Attitudes, Fishbein Models, Factor Analysis, ANOVA